Barriers to information resource utilization and information-seeking behaviours among law students at the University of Benin, Benin City, Nigeria - Ossai-Ugbah, Ngozi Blessing (Communicate: Journal of Library and Information Science, 2025)
The study investigated the problems militating against the utilization of information resources / services by undergraduate law students of University of Benin, Benin City. The sample population consisted of 230 undergraduate law students randomly selected from the first to fifth year of study from a population of 1145. Their information seeking activities were tested to discover how undergraduate law students seek information. This is a descriptive survey research; therefore, the researcher employed a descriptive design. The instrument used for data collection was questionnaire and percentage. The Simple Percentage Analysis and the Z-Test analysis were used in data analysis. The study found that male students consult the librarian, there is no difference in the information seeking pattern of male and female law students, and law students have inadequate ICT skills. The recommendation include: that school authority stock the library with relevant and up-to-date materials, and ICT should be made a core part of law student’s curriculum.